Doctoral Dissertations by College of The Bahamas Faculty or about The Bahamas, 2008-2012 - Walker, Berthamae L. (International Journal of Bahamian Studies, 2012)
It has been four years since the International Journal of Bahamian Studies last published a compilation of doctoral dissertations written by College of the Bahamas faculty or dissertations by scholars worldwide with content relevant to Bahamian studies.